2017
DOI: 10.1186/s40066-017-0101-0
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and food security effects of using of certified seed potato: the case of Kenya’s potato farmers

Abstract: Background: Potato is a major food crop in the tropical regions of Africa. However, potato yields continue to remain very low in these regions mainly due to use of poor quality seed. The recent development of rapid seed multiplication technique has helped to shorten the duration of certified seed potato (CSP) production and increase the supply of seed. This study assessed the effect of using CSP on yield, input use, and food security among smallholder farmers. It focused on potato growers in central highlands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 14 publications
1
32
0
2
Order By: Relevance
“…All the farmers used own farm saved seed tubers while few accessed certified seed potato from research institutions. These results corresponds to the findings by [4,5] who reported that the informal seed system is the main means of seed acquisition in Eastern Africa and over 98% of the farmers used seed potato either from either own fields, neighbours and local markets. In addition, [18] and [35] reported that less than 5% of farmers in Eastern Africa used certified seed potato.…”
Section: Seed Potato Production Practices By Small-scale Farmerssupporting
confidence: 74%
See 4 more Smart Citations
“…All the farmers used own farm saved seed tubers while few accessed certified seed potato from research institutions. These results corresponds to the findings by [4,5] who reported that the informal seed system is the main means of seed acquisition in Eastern Africa and over 98% of the farmers used seed potato either from either own fields, neighbours and local markets. In addition, [18] and [35] reported that less than 5% of farmers in Eastern Africa used certified seed potato.…”
Section: Seed Potato Production Practices By Small-scale Farmerssupporting
confidence: 74%
“…Some farmers had been involved in potato production for a short duration suggesting diversification of crops from subsistence to market based farming as they increasingly took up production of the crop [10,32]. Studies by [4] revealed high profits accrued from potato production for those farmers who have access to certified seed potato and shifted potato production from subsistence to agribusiness. Longer duration of involvement in potato production could be attributed to higher yields of potato compared to cereals in a limited land area in these agro-ecologies [8].…”
Section: Seed Potato Production Practices By Small-scale Farmersmentioning
confidence: 99%
See 3 more Smart Citations